Technological priorities for the development of Russia’s industrial sector in the context of deep digital penetration - O. E. Pudovkina (Вестник университета)
Industry 4.0 dictates certain requirements for the modernisation of processes and production facilities. This is especially true for industry, which has a relatively high share of the country’s gross domestic product The outline of the future strategic development of the industry sector in an environment of external change is therefore of particular relevance. The purpose of the study is to forecast technology priorities and possible stages of development of advanced manufacturing technologies in Russia. The main research method is foresight methodology, based on long-term integrated assessment models of global production and technology market development in scenario form. This method has allowed to identify the most functional information resources needed for this study. The article presents a methodology for systemic anticipation of long-term technological change to update the strategic vector of industrial development, which is consistent with the context and content of the country’s industrial policy. The study resulted in a comprehensive forecast of possible stages in the development of advanced production technologies and the anticipation of the priority of technological changes to modernise the industrial complex in the context of deep digital penetration, based on the concept of a new industrial society.